Cytotoxic polycyclic polyprenylated acylphloroglucinol derivatives and xanthones from Hypericum attenuatum. (March 2016) - Zhou, Zhong-Bo; Zhang, Yang-Mei; Luo, Jian-Guang; Kong, Ling-Yi
Graphical abstract: Highlights: Two new polycyclic polyprenylated acylphloroglucinols and five known compounds were isolated. The structure elucidation was achieved by spectroscopic measurements including 2D-NMR spectroscopy. Some compounds exhibited significant cytotoxic activities and nitric oxide production inhibitory activity. Abstract: Two new polycyclic polyprenylated acylphloroglucinols, attenuatumione G (1 ) and attenuatumione H (2 ), together with five known compounds (3 –7 ) have been isolated from the whole plant of Hypericum attenuatum . Their structures were elucidated by spectroscopic data including HRESIMS, 1D- and 2D-NMR. In biological assays, compound2 showed moderate cytotoxic activities against Hep-G2 (IC50 9.11 μM) and MCF-7 (IC50 16.24 μM), compound4 exhibited significant cytotoxic activity with IC50 value of 5.32 μM against Hep-G2, and both compounds5 and6 revealed significant nitric oxide production inhibitory activity with IC50 values of 5.52 and 8.46 μM, respectively.